Key drivers affecting the spatial heterogeneity of the regeneration process in old-growth beech forests in southeastern Europe - Kanjevac, Branko; Babić, Violeta; Stajić, Snežana; Martać, Nikola; Pavlović, Branka; Furtula, Danilo; Čokeša, Vlado (Frontiers in Forests and Global Change, 2023)
Understanding the processes occurring in old-growth forests and identifying their key aspects can significantly enrich modern forestry practices with innovative ideas and concepts. The natural regeneration process in beech old-growth forests exhibits distinct spatial heterogeneity and temporal variability. To define the key drivers that influence the spatial heterogeneity of regeneration processes and their effects, research was conducted in three beech old-growth forests situated in Serbia, Southeastern Europe: Felješana, Vinatovača, and Kukavica. In each old-growth forest, a network of circular sample plots with an area of 0.1 ha (totaling 45 plots) was established to gather data on structural characteristics and ecological conditions. Within each circular sample plot, data on the regeneration layer were collected on four square sample plots of 1 m2 (180 in total). Using linear mixed models, the key drivers of spatial heterogeneity of regeneration processes in beech old-growth forests were analyzed. Based on the results, several key factors contribute to the highly heterogeneous distribution of seedlings, including the canopy, the presence of a middle layer comprising young trees, ground vegetation, and soil stoniness, while a significant influence of the combined effect of the canopy and the presence of a middle layer of young trees is also defined. The spatial heterogeneity of the regeneration process is also represented through the assessment of the ratio between the abundance of one-year-old and older seedlings. The dominance of one-year-old seedlings intensifies with increased canopy density (in instances of very dense canopy (1.0), the ratio of one-year-old and older seedlings is 70:30%). Seedling growth characteristics are shaped by multiple factors, including the influence of the canopy, the presence of the middle layer of young trees, slope, and soil stoniness, with a substantial combined influence of the canopy and the middle layer of young trees. This indicates that the spatial variability of the regeneration process in beech old-growth forests is primarily driven by factors with a substantial individual influence, which may also act combined. It is of paramount importance to understand these factors and determine their influence on the regeneration process in managed beech forests.